Electrophysiological correlates of character transposition in two-character Chinese word identification. (November 2021) - Zhang, Er-Hu; Lai, Xue-Xian; Li, Defeng; Lei, Victoria Lai Cheng; Chen, Yiqiang; Cao, Hong-Wen
Abstract: The present study investigated brain activity elicited by character transposition processing of two-character Chinese words using event-related potentials (ERPs) with a two-target rapid serial visual presentation (RSVP) task. The behavioral results showed higher accuracy with canonical and transposed words than pseudowords in the short stimulus onset asynchrony (SOA, 249 ms) condition, but not in the long SOA (581 ms) condition. Additionally, relative to the pseudoword condition, the ERP results indicated that the canonical and transposed words elicited statistically less negative N250 and N400 amplitudes. Furthermore, both the canonical and transposed words revealed no significant differences in the early N100, P200, and N250 components, whereas a significant difference was observed in the N400 amplitude regardless of the SOAs between the two constituent characters, indicating less semantic activation. Taken together, our electrophysiological data indicate that early ERP components are not sensitive to Chinese character transposition. In contrast, such morpheme transposition affects the semantic processing of Chinese compound words. Highlights: No differences for N100, P200 and N250 amplitudes between canonical and transposed words Early ERP components are not sensitive to Chinese character transposition Transposed words exhibit a more negative N400 amplitude than canonical words Character transposition affects the lexical representation of compound word in the RSVP task